OUTLINES OF THE GAMER DATA SUBJECT POSITION AND ITS IMPLICATIONS FOR TRUST - Schellewald, Andreas; Su , Chunmeizi (AoIR Selected Papers of Internet Research, 2026)
In this paper, we outline the data subject position of the gamer within the contemporary media landscape, looking at gamers not just as players but as a broader position of social media and internet users. We draw on findings from a more extensive project investigating privacy, trust, and data literacy in online gaming to do so. More specifically, we draw on a formative analysis of the data practices of 37 multiplayer online games (e.g., League of Legends), gaming distribution platforms (e.g., Steam), and online community sites (e.g., Discord). Through the privacy policies of these platforms, and adjacent case study analyses of controversies related to data practices, the paper studies the network structures in which the gamer data subject exists. By examining these relationships, the paper sheds light on how gamers and gaming are governed by the technological and policy architectures of platforms. In particular, we highlight three critical dimensions herein. Firstly, we examine forms of dependency through which gamers are bound to datafication processes to access online gaming spaces. Secondly, we foreground how platforms rely on behavioural profiling and algorithmic categorisation to commodify players' interactions. Lastly, we underline a systemic reliance on third-party actors such as advertisers, payment processors, and data brokers, linking the gaming data subject to more expansive societal fields. Doing so, we position the gamer data subject as a nexus for future comparative resrach on cultures of trust and user privacy in gaming.